2020
DOI: 10.1097/tp.0000000000003230
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Outcomes of Kidney Transplants From Very Small (≤15 kg) Pediatric Donors With Acute Kidney Injury

Abstract: Background. Kidneys from small deceased pediatric donors with acute kidney injury (AKI) are commonly discarded owing to transplant centers’ concerns regarding potentially inferior short- and long-term posttransplant outcomes. Methods. We retrospectively analyzed our center’s en bloc kidney transplants performed from November 2007 to January 2015 from donors ≤15 kg into adult recipients (≥18 y). We pair-matched grafts from 27 consecutive donors with AKI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Jiang et al [ 25 ] found that transplants procured from pediatric AKI donors have a comparable renal function and an excellent patient and graft survival rate, but they found a similar incidence of DGF, which is different from our study. In contrast, our study consists with another study includes very small (≤ 15 kg) pediatric donors with AKI and found that AKI can impact early post-transplant kidney graft function (e.g., the rate of DGF), but it did not increase the risk of early graft loss or decreased renal function in the long term [ 18 ]. A national study of pediatric KT recipients from a donor with AKI found that donor AKI status or increased peak and terminal creatinine levels do not affect the rate of DGF in pediatric KT recipients [ 17 ].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Jiang et al [ 25 ] found that transplants procured from pediatric AKI donors have a comparable renal function and an excellent patient and graft survival rate, but they found a similar incidence of DGF, which is different from our study. In contrast, our study consists with another study includes very small (≤ 15 kg) pediatric donors with AKI and found that AKI can impact early post-transplant kidney graft function (e.g., the rate of DGF), but it did not increase the risk of early graft loss or decreased renal function in the long term [ 18 ]. A national study of pediatric KT recipients from a donor with AKI found that donor AKI status or increased peak and terminal creatinine levels do not affect the rate of DGF in pediatric KT recipients [ 17 ].…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have reported worse clinical outcomes when deceased donor kidneys with AKI were used [ 14 , 15 ]. When considering donors, AKI can activate body repair processes and initiate ischemic preconditioning, which can be beneficial for graft function repair in the recipient [ 4 , 16 ], and the kidneys procured from pediatric deceased donors may have greater repair potential because the donors are younger, with fewer underlying disease or comorbidities [ 17 , 18 ]. However, there are scant data and allocation practices on the results of pediatric AKI deceased donor kidney transplantation, and the reliability of pediatric donors with AKI remains controversial [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies performed by the same group likely included the same patient population. 79,80 Another study analyzed a series of 30 en block kidney transplantations, comparing outcomes of recipients receiving organs from donors weighing either <5 or >5 kg. 81 The <5-kg group constituted of 8 donors, 7 of whom were in the neonatal period.…”
Section: Kidneysmentioning
confidence: 99%
“…At long‐term follow‐up, no difference in graft survival or function could be observed when comparing DBD with DCD recipients. Two other studies performed by the same group likely included the same patient population 79,80 …”
Section: Introductionmentioning
confidence: 99%